Sulfide immiscibility induced by wall-rock assimilation in a fault-guided basaltic feeder system, Franklin Large Igneous Province, Victoria Island (Arctic Canada) - Hayes, Ben; Bédard, Jean H.; Hryciuk, Matthew; Wing, Boswell; Nabelek, Peter; MacDonald, William D.; Lissenberg, Cornelis Johan (Economic Geology, 2015)
The Southern Feeder Dike Complex is part of the Franklin Large Igneous Province (LIP), exposed in the Minto Inlier of Victoria Island in the Canadian Arctic. Previous field and geochemical studies on the Franklin LIP considered its igneous rocks to be prospective for Fe-Ni-Cu mineralization. The Southern Feeder Dike Complex comprises a series of NW-SE-trending gabbroic intrusions and sedimentary hosts. Field and textural relationships show that the Complex intrusions were emplaced contemporaneously with Neoproterozoic normal faulting. Faulted contact zones correspond to prominent first derivative magnetic lineaments. Gabbroic dikes have intrusive contacts against brecciated country rock, and diabasic microxenoliths in basaltic matrices indicate multiple intrusive/brecciation events. Intrusive breccias are commonly overprinted by hydrothermal greenschist facies assemblages, with calcite + pyrite veins filling open spaces between breccia fragments. Late dikes emplaced into these heterogeneous breccias contain disseminated globular and net-textured sulfides suggesting that sulfide immiscibility was triggered on a local scale by assimilation of local wall rock. This inference is supported by elevated δ34S values of sulfides in these dikes, consistent with assimilation of country rocks. Wall-rock assimilation would have been facilitated by fault-related brecciation and cataclasis, which would expose extensive xenolith surface areas to fresh magma. Gossanous and meter-scale semimassive sulfide showings associated with dikes and sills located upsection from the Southern Feeder Dike Complex suggest that immiscible sulfide liquids may have been flushed downstream (or upsection) during replenishment of composite dike systems. Fault-mediated melt ascent along northwest-southeast faults has been documented elsewhere in the Minto Inlier, providing equivalent opportunities for wall-rock assimilation and consequent triggering of sulfide immiscibility and sulfide melt redistribution. The evidence preserved in the Complex ...